A Study Of Capacitance-Voltage Characteristics For Metal-Oxidesemiconductor Structure On Goldcompensated High Resistivity Silicon - Tan, Jia Yiing (Universiti Sains Malaysia, 2017)
The goal to achieve low microwave attenuation loss in a high-speed wireless communication system is crucial for the advancement of technology evolution. Background carrier and parasitic surface conduction hinder the progression of a wireless system to perform better. Recently, a new method using deep-level doping compensation with the gold element to create high resistivity silicon substrate for microwave application is successful. Currently, there is no existing equivalent circuit model and mathematical equations to classify capacitance-voltage characteristic for a metal-oxide structure on gold-compensated high resistivity silicon substrate. An investigation of capacitancevoltage characteristics for the metal-oxide-semiconductor structure on low resistivity, high resistivity and gold-compensated silicon substrates are carried out. The suitable mathematical equations to represent capacitance-voltage curves of low resistivity silicon is evaluated. High resistivity silicon equivalent circuit models for low and high frequencies are determined in MATLAB and verified in SILVACO. The equivalent circuit models and equations of high resistivity silicon are determined successfully. Experimental data of Au-compensated high resistivity silicon is compared and analysed with theoretical high resistivity silicon data. Based on the comparison result of both C-V curves, the equivalent circuit of gold-compensated high resistivity silicon is not same as the high resistivity silicon.